At Westonci.ca, we provide reliable answers to your questions from a community of experts. Start exploring today! Explore thousands of questions and answers from a knowledgeable community of experts on our user-friendly platform. Join our platform to connect with experts ready to provide precise answers to your questions in different areas.
Sagot :
Answer:
y = - 4
Step-by-step explanation:
Given
y = 2x + ( - 2) , that is
y = 2x - 2 ← substitute x = - 1
y = 2(- 1) - 2 = - 2 - 2 = - 4
This is confirmed by the point (- 1, - 4 ) on the graph
X = -1
So if you Plug that in to your problem it is shown as y=2(-1)+-2.
2•-1 is -2 and when added to -2 you answer is -4.
Y=-4
So if you Plug that in to your problem it is shown as y=2(-1)+-2.
2•-1 is -2 and when added to -2 you answer is -4.
Y=-4
Thank you for your visit. We're committed to providing you with the best information available. Return anytime for more. We appreciate your visit. Our platform is always here to offer accurate and reliable answers. Return anytime. We're glad you visited Westonci.ca. Return anytime for updated answers from our knowledgeable team.